Técnica de medição tri-dimensional baseada no aprimoramento da formulação da técnica de Moiré de projeção e recursos de fotogametria - Gustavo Santos Borges (2011)
The current research established a new free-surface measurement technique based on Projection Moiré improvements and stereoscopy features. The mainly proposed improvements are: the camera calibration techniques were incorporated in order to improve the original triangulation step, a new technique to define the projector and reference plane equation was established. The current research also extends the parallax between the stereoscopy technique and Projection Moiré technique to triangulation standpoint. The proposed measurement technique and the Projection Moiré technique were compared over metrological and time processing standpoint. It was noted that proposed measurement technique is more accurate than Projection Moiré technique; an uncertainty decreasing from 2.24% to 1.05% was calculated. The proposed measurement technique is also less sensitive to camera lens distortions, in contrast the triangulation step requires silently more computational effort, and increase from 0.48s to 0.63s was noted. The proposed measurement technique was qualitatively evaluated in order to show that it is appropriate to measurement several material types and shapes. They were evaluated: Plastic part, human hand, porcine leaflet, ceramic tea cup, and human face. The results stated that technique was effective. Based on results, it was concluded that the proposed measurement technique is an excellent option to free surface evaluation and is better that Projection Moiré over accuracy stand point, moreover, extend the parallax between the fringe projection techniques and stereoscopy to triangulation step.